Effect of early posthatch supplementation of vitamin E and omega-3 fatty acids on the severity of wooden breast, breast muscle morphological structure, and gene expression in the broiler breast muscle - Ji Wang; Daniel L. Clark; Sheila K. Jacobi; Sandra G. Velleman (Poultry Science, 2020)
Wooden breast (WB) has arisen primarily in the breast muscle of commercial broilers. It is characterized by palpation of a rigid pectoralis major (p. major) muscle and is under severe oxidative stress and inflammation. Previous studies have shown that vitamin E (VE) has antioxidant properties and omega-3 (n-3) fatty acids have an anti-inflammatory effect. The objectives of this study were to identify the effects of VE and n-3 fatty acids on the severity of WB, morphological structure of the p. major muscle, expression of genes likely associated with WB and to determine the most beneficial supplementation period. A total of 210 Ross 708 broilers were randomly assigned into 7 treatments with 10 replicates of 3 birds each. The control group received a corn–soybean meal basal diet during the entire study (0–58 d). Supplementation of VE (200 IU/kg), n-3 fatty acids (n-6/n-3 ratio of 3.2:1), or combination of both were fed during the starter phase (0–10 d) or grower phase (11–24 d). All broilers were harvested at 58 d of age. Morphological assessment of the p. major muscle included myofiber width, perimysial and endomysial connective tissue space, overall morphological structure, and scoring of WB microscopically. Gene expression was measured using nanostring analysis. Genes associated with muscle development and growth factors, inflammation, extracellular matrix, and glucose metabolism were differentially expressed in the p. major muscle of the broilers supplemented with VE in the grower diet. Greater than 2 times more giant myofibers (≥70 μm) were found in the group supplemented with VE and n-3 fatty acids in the starter diet compared with the group fed VE in the grower diet (P = 0.02). Microscopic evaluation showed that VE supplementation in the grower diet had a 16.19% increase in muscle with no WB compared with the control group (P = 0.05). These data suggest that supplementation of VE during the grower phase may reduce the severity of WB in broilers.